SEASONAL VARIATIONS IN THE TOTAL CHOLESTROL CONTENT OF THE LIVER OF CAT FISH. HETEROPHUESTES FOSSILIS (BLOCH). - SHRENI, KALPANA D; JAFRI, A K (Fishery Technology, 2017)
Variations in the total liver cholesterol content of Heteropnuestesfossilis followed weH defined seasonal cycle. A declinewas recorded during the period when the gonads were passingthrough the peak ripe stage. The highest value of the cholesterolwas however attained before this phase of gonad maturation~Concentration pattern of liver cholesterol seemed related tovariations in the cholesterol metabolism of the fish, necessitated,besides other factors, by the demand for sex hormones. Apossibility of the influence of feeding intensity on liver cholesterolcontent has also been indicated.